2018
DOI: 10.19044/esj.2018.v14n30p323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and Antibiotic resistance profiles of Escherichia coli extended-spectrum β-lactamases producer strains isolated from urine samples in Benin

Abstract: Urinary tract infections are the second common reason of medical consultations and antibiotics prescription. Escherichia coli is known to cause most urinary tract infections. The aim of this study was to characterize and determine the antibiotic resistance profile of E. coli extended-spectrum βlactamases (ESBL) producer strains isolated from urine samples. The urine samples collected came from hospitalized and non-hospitalized patient referred to Hubert Koutoukou Manga (HKM), National and University Hospital C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
0
1
Order By: Relevance
“…As for ESBL-encoding genes, they consisted of bla CTX-M-1 group ESBL in 92.3% (12/13) of our ESBLproducing isolates. This frequency of CTX-M-1 type ESBL is similar to the one found previously in Burkina Faso (94%), by Ouedraogo et al, 2016 [15] and it is congruent with the report of the same author [9] that CTX-M-15 is the most frequent ESBL found in West-Africa, as well as in many other parts of the world [3,4,20,21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As for ESBL-encoding genes, they consisted of bla CTX-M-1 group ESBL in 92.3% (12/13) of our ESBLproducing isolates. This frequency of CTX-M-1 type ESBL is similar to the one found previously in Burkina Faso (94%), by Ouedraogo et al, 2016 [15] and it is congruent with the report of the same author [9] that CTX-M-15 is the most frequent ESBL found in West-Africa, as well as in many other parts of the world [3,4,20,21].…”
Section: Discussionsupporting
confidence: 91%
“…The migration of PCR products from our ESBL strains demonstrated the production of two types of narrow-spectrum beta-lactamases: the TEM (53.8%), and OXA (61.5%). This is lower than a previous report by Mousse et al, 2018 [20] where 100% of TEM type beta-lactamase were found in a similar study of ESBL E. coli genes isolated from urine samples in Benin. Additionally, Kpoda et al, 2018 [21] found an overall 24.6% prevalence of TEM encoding genes in E. coli isolates obtained from urine, pus, blood, stool, vaginal swab and pleural fluid samples of patients attending three major hospitals in the capital of Burkina Faso, which indicates a variability in the distribution of these genes among E. coli in Africa.…”
Section: Discussioncontrasting
confidence: 69%